Volume 2: Structures, Safety and Reliability 2008
DOI: 10.1115/omae2008-58053
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Approaches to Storm Statistics in the Ocean

Abstract: The classical approach to storm statistics in the ocean is an Eulerian analysis of wave time series at a given location, in which the wave data can be observations or results of wave models. The information obtained from this approach is storm frequency, duration and intensity, from which extremes at the particular location can be estimated. The availability of spatial information of wave characteristics at successive time intervals, which is available from large scale forecasts or hindcast allows the follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…While storms move and change direction, some of the storm statistics are based on data from a single location not following the storm as discussed in Bernardino et al (2008). A noticeable shift of the location of the North Atlantic storm tracks was found in McCabe et al (2001) who showed that storm frequency in midlatitudes decreased during the second half of the twentieth century while an increase was found for the high latitudes north of 60°N.…”
Section: Introductionmentioning
confidence: 97%
“…While storms move and change direction, some of the storm statistics are based on data from a single location not following the storm as discussed in Bernardino et al (2008). A noticeable shift of the location of the North Atlantic storm tracks was found in McCabe et al (2001) who showed that storm frequency in midlatitudes decreased during the second half of the twentieth century while an increase was found for the high latitudes north of 60°N.…”
Section: Introductionmentioning
confidence: 97%
“…Storms evolve in space and time often changing direction and thus one can choose an Eulerian or a Lagrangian description to model them as discussed by Bernardino et al (2008). However it is most common to adopt the Eulerian approach, which is the one considered in this paper.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the scarcity of these events, they can be associated with severe consequences such as considerable damages to ships, offshore structures and potential loss of human life (Faulkner and Buckley 1997;Guedes Soares et al 2008). The statistical wave data used in climatic databases are normally at selected grid points, but to study the effect of a specific storm, a different approach needs to be adopted (Bernardino et al 2008). …”
Section: Introductionmentioning
confidence: 99%